Dynamics of lithospheric extension: a modeling study - Govers, R.M.A. (Utrecht University, 1993)
Much of the work on continental margins and sedimentary basins has been directed at quantifying parameters of the pure shear extension model (or stretching model) (McKenzie, 1978). This is surprising, since a sound physical basis of this kinematic model is lacking. Alternative kinematic models, like the simple shear model (Wernicke, 1981) have been proposed which, at least in some basins, explain the surface observations equally welL In terms of asymmetry, the pure shear model and the simple shear model represent end-members of a spectrum of kinematic models for continental extension (Figure 1). The central issue of this thesis is to determine -by numerical modeling- whether the pure shear model and the simple shear model are physically plausible and to gain insight in the physical conditions which control the style of extension.
Keywords: Aardwetenschappen